2008
DOI: 10.1007/s11423-008-9088-3
|View full text |Cite
|
Sign up to set email alerts
|

Computer-supported aids to making sense of scientific articles: cognitive, motivational, and attitudinal effects

Abstract: High school students can access original scientific research articles on the Internet, but may have trouble understanding them. To address this problem of online literacy, the authors developed a computer-based prototype for guiding students' comprehension of scientific articles. High school students were asked to read an original scientific research article about the effects of drug or alcohol abuse, which was presented on a computer screen either with computer-based comprehension aids or without aids. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
1
14
0
2
Order By: Relevance
“…The analysis of the results indicate that the use of scientific articles as learning resources allowed the students to analyze the experimental data and to go as deeply into the content as they wanted, and possibly improved students' problem-solving skills, as already reported by other studies in the literature [8,9,15,24]. The use of these articles seems to have helped to improve students' ability to gain command of biochemical concepts that are fundamental to the understanding of metabolism.…”
Section: (9%)supporting
confidence: 56%
See 2 more Smart Citations
“…The analysis of the results indicate that the use of scientific articles as learning resources allowed the students to analyze the experimental data and to go as deeply into the content as they wanted, and possibly improved students' problem-solving skills, as already reported by other studies in the literature [8,9,15,24]. The use of these articles seems to have helped to improve students' ability to gain command of biochemical concepts that are fundamental to the understanding of metabolism.…”
Section: (9%)supporting
confidence: 56%
“…In this regard, series of questions were designed in such a way that students were oriented to read/consult specific parts of the articles, either the article data or specific parts of the text. Gegner et al [15] showed that highlighting specific parts of the text to guide students' attention was effective for enhancing students' comprehension of research literature and also for guiding cognitive processing, which is required for meaningful learning. We found that this 4 (5%) ''The site was out a few times'' (P.32).…”
Section: Students' Perception Of the Use Of Scientific Articles As A mentioning
confidence: 99%
See 1 more Smart Citation
“…Of the five studies found in this review, only one (Gegner et al, 2009) Another explanation concerns the predominant focus on struggling readers in most articles reporting reading comprehension interventions. Of the five studies found in this review, only one (Gegner et al, 2009) Another explanation concerns the predominant focus on struggling readers in most articles reporting reading comprehension interventions.…”
Section: Discussionmentioning
confidence: 96%
“…previous reports and studies have strongly suggested that technologies and mobile games should be integrated into mathematics teaching and learning, since these technologies are a promising means for providing conceptual understanding [11]. Integration of technologies into mathematics classroom settings can enhance student"s mathematics learning, since the technologies can provide dynamic visualization and interactivity that can help student learn mathematics effectively [12].…”
Section: Introductionmentioning
confidence: 99%